The Lived experiences of young adult sole breadwinner in the Filipino families - Acosta, Camille Alyssa; Antido, Rogelen V.; Magrurulang, Rhea F.; Vidad, Dianne Marie V. (Manila : National University, 2021)
In a Filipino family. the role of the breadwinner is to provide the family's physiological needs - food, shelter, clothing and ensure the family's health and safety.
Chapter 1. Introduction -- Chapter 2. Review of related literature -- Chapter 3. Methodology -- Chapter 4. Results and discussion -- Chapter 5. Summary, Conclusion and recommendation -- References -- Appendices.
Includes bibliographical index.
Keywords: FAMILY